Analysis of an N/G/1 finite queue with the supplementary variable method. (1999) - Lee, Gyemin; Jeon, Jongwoo
Abstract : In this paper, we suggest a new approach to the analysis of an N / G / 1 finite queue with the supplementary variable method. Compared to the conventional approach, our approach yields a simpler formula for the queue length distribution, which in turn gives a more efficient computational algorithm. Also, the new approach enables us to derive the joint density of the queue length and the elapsed service time.